2003
DOI: 10.1111/j.1749-6632.2003.tb03226.x
|View full text |Cite
|
Sign up to set email alerts
|

New Models to Investigate Mechanisms of Disease Genesis from Primitive BCR‐ABL+ Hematopoietic Cells

Abstract: Three years ago we described a novel autocrine IL-3/G-CSF mechanism active in the leukemic CD34(+) cells from chronic myeloid leukemia (CML) patients in chronic phase (PNAS 96: 12804-12809, [1999]). We also showed that exposure of the most primitive CD34(+) cells from normal human bone marrow to excess IL-3 stimulates not only the division of these cells but also their differentiation. In contrast, both IL-3 and G-CSF cause an expansion of the more mature types of normal CD34(+) progenitors. These findings sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…[11][12][13][14] Furthermore, aberrant production of G-CSF has been tightly linked to tumor generation and progression in many tumor types. [7][8][9][10][11][12][13][14][15] Recent studies have found that G-CSF regulates proliferation and differentiation of neural stem cells (NSCs), 16,17 induces STAT 3 activation and downstream genes expression. The present results suggest that G-CSF signaling participates in the progression of glioma, and that it plays an important role in the generation and recurrence of glioma.…”
Section: Granulocyte-colony Stimulating Factor Promotes Proliferation Migration and Invasion In Glioma Cellsmentioning
confidence: 99%
“…[11][12][13][14] Furthermore, aberrant production of G-CSF has been tightly linked to tumor generation and progression in many tumor types. [7][8][9][10][11][12][13][14][15] Recent studies have found that G-CSF regulates proliferation and differentiation of neural stem cells (NSCs), 16,17 induces STAT 3 activation and downstream genes expression. The present results suggest that G-CSF signaling participates in the progression of glioma, and that it plays an important role in the generation and recurrence of glioma.…”
Section: Granulocyte-colony Stimulating Factor Promotes Proliferation Migration and Invasion In Glioma Cellsmentioning
confidence: 99%